Pseudo-pericarditis in two cows with tropical theileriosis: clinical, haematological and biochemical findings - DEĞIRMENÇAY, Ş.; KIRBAŞ, A.; YANAR, K.E.; EROĞLU, M.S. (Journal of the Hellenic Veterinary Medical Society, 2021)
Pseudo-pericarditis-shaped theileriosis is a rare phenomenon that only a handful of reports have been introduced. This case report aims to describe pseudo-pericarditis due to tropical theileriosis diagnosed in a 7-year old crossbreed Simmental cow and 3-year old crossbreed Holstein cow with a loss of appetite, weakness, and weight loss. We have detected high fever, paleness in mucous membranes (anaemia), petechial haemorrhages and icterus, an obvious enlargement in the left prescapular lymph node, distension in the jugular venous and positive venous pulse in the clinical examination. The factors of Theileria annulata were intensively present in the microscopic investigation of the peripheral blood smears of both animals. We determined considerably low levels of hematologic parameters. Finally, biochemical analyses revealed the elevated concentration of cTn-I, activities of CK-MB, LDH, AST, GGT, and the levels of TBIL. On the contrary, levels of TP, ALB, GLU, and Ca were significantly low. In this case report, we would like to touch upon some points that were not mentioned or merely investigated in the previous studies. In this context, we will first argue the increased risk of occurrence of pseudo-pericarditis in case of severe anaemia, petechial haemorrhages in conjunctival mucosa, greatly enlarged superficial lymph nodes and considerably low numbers of haematocrit. We also think that pseudo-pericarditis is a late-stage symptom of theileriosis. Then we further elaborate on the relationship between severe anaemia, pseudo-pericarditis and myocardial damage by referring to cardiac biomarkers (cTnI, CK-MB etc.) which was never done before. Later, we will finally elucidate on the biochemical parameters (AST, LDH, ALB, TBIL etc.) which revealed hepatic damage. Finally, we argue that in case of severe anaemia along with the expansion in vena jugularis and positive venous pulse, pseudo-pericarditis should be taken into consideration for the cows with tropical theileriosis.